Leveraging Information Technology Towards Enhancing Patient Care and a Culture of Safety in the U.S. - Ball, M. J.; Garets, D. E.; Handler, T. J. (Methods of Information in Medicine, 2003)
Objectives: To heighten awareness about the critical issues currently affecting patient care and to propose solutions based on leveraging information technologies to enhance patient care and influence a culture of patient safety.Methods: Presentation and discussion of the issues affecting health care today, such as medical and medication-related errors and analysis of their root causes; proliferation of medical knowledge and medical technologies; initiatives to improve patient safety; steps necessary to develop a culture of safety; introduction of relevant enabling technologies; and evidence of results.Results and Conclusion: Medical errors affect not only mortality and morbidity, but they also create secondary costs leading to dissatisfaction by both provider and patient. Health care has been slow to acknowledge the benefits of enabling technologies to affect the quality of care. Evaluation of recent applications, such as the computerized patient record, physician order entry, and computerized alerting systems show tremendous potential to enhance patient care and influence the development of a culture focused on safety. They will also bring about changes in other areas, such as workflow and the creation of new partnerships among providers, patients, and payers.
Keywords: Medical errors; patient safety; information technology; computerized patient record; physician order entry; clinical decision support; clinical outcomes; evidence-based medicine